Kontribusi Logika Dalam Perspektif Humanistik Yang Holistik - Noverlina Zendrato; Susiana Lase; Mozes Lawalata (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
In the holistic humanistic perspective, logic plays an important role in understanding and developing human thinking. Logic helps individuals to think comprehensively and thoroughly, considering all possibilities from various aspects and perspectives. In the context of education, logic helps teachers and educators to understand and appreciate the uniqueness of individuals. Logic also helps in understanding the relationships between various elements in life, such as religion, education, and human existence. In the holistic perspective, logic helps humans to see everything as interconnected and having meaningful synergies. Logic helps individuals to think holistically and comprehensively, thus enabling them to understand the relationships between various aspects of life. In the humanistic perspective, logic is also used as a tool to achieve self-actualization, free will, and self-efficacy. Therefore, logic has a significant contribution in the holistic humanistic perspective by assisting in understanding, self-development, and comprehensive thinking.